SIKAP PESERTA DIDIK KATOLIK DALAM MENJUNJUNG TINGGI KELUHURAN MARTABAT MANUSIA DI SMA NEGERI 1 TABANG - Afrianus Darung (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2024)
This research was conducted at Tabang State Senior High School to explore attitudes towards upholding human dignity among Catholic students. Qualitative methods were used with interviews, observation, and documentation on Catholic students, Catholic Religion teacher, Guidance Counselling teacher, and deputy principal. Analysis and descriptive analysis were carried out on the collected data. The findings show the attitudes expressed by students towards human dignity, namely: (1) Self-acceptance with an attitude of gratitude, self-confidence and ability development. (2) Respect for teachers by greeting each other and behaving politely. (3) Recognition of the strengths of fellow students by sharing knowledge and experience. (4) Empathy by helping others in difficult situations. (5) Brotherhood among students with an attitude of mutual cooperation and sharing in the school environment. This research illustrates the importance of maintaining an attitude of respect for human dignity, both towards oneself and others, in character formation in the educational environment.